PORTFOLIO AS AN INSTRUMENTAL MEANS OF SELF-EVALUATION OF EDUCATIONAL AND PROFESSIONAL ACHIEVEMENTS OF STUDENTS - E. F. Zeer; L. N. Stepanova (Russian State Vocational Pedagogical University, 2018)
Introduction. In the context of the reformation of the higher education system, the shift of academic education towards the practical sphere of future professional activity bring onto focus the quest for new, more objective methods and means of assessing the results of educational and professional activities of students. In this connection, one of those is the portfolio which enables to evaluate not only the level of knowledge, but also the individual progress of the student.The aim of the publication is to discuss the opportunities and the role of the portfolio in the development of professional competence of university students.Methodology and research methods. At the theoretical level, the article provides a retrospection of the concept of the portfolio in domestic and foreign science. Empirical research was carried out with the use of such psychodiagnostic techniques as the method of "Motivation of Professional Activity" by K. Zamfir in modification of A. Rean; the questionnaire "Reflexivity" by A. V. Karpov; the questionnaire "Style of Behaviour Self-Regulation" by V. I. Morosanova. The obtained data were processed by means of the methods of mathematical statistics based on the Student's T-Test.Results and scientific novelty. The article analyzes the advantages of using the portfolio in terms of higher education. It is proved that the process of portfolio development involves not only the demonstration of the student's efforts and achievements in a particular activity, but also contributes to the development of analytical abilities, by comparing the results of their own activities with the established standards. The use of the portfolio contributes to the solution of significant pedagogical tasks, such as stimulating motivation for learning, striving for a high level of achievement, the development of reflective and evaluation skills. It is highlighted that functionally the portfolio can serve as the tool of both the analysis of educational and professional achievements of students, and forecasting of their professional future. The sample of students of Kuibyshev Branch of Novosibirsk State Pedagogical University demonstrated the relationship between the active use of portfolio technology and the positive dynamics of parameters for professional development of students, namely regulatory, motivational and reflective components.Practical significance. The results of the study can be considered as a contribution to the scientifically based ideas about the use of portfolio technology in the practice of the Russian higher education. The data obtained in the course of the study can be used by representatives of the vocational education system, tutors engaged in psychological and pedagogical support of university students.